Pemanfaatan Barang Habis Pakai sebagai Media Pembelajaran untuk Menunjang Kreativitas Siswa Kelas 10 SMK Swasta Pelita Bulu Cina - Aulia, Zulfi; Siregar, Zulham; Novianti, Yusda (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
The utilization of consumables as an educational tool presents an avenue for fostering student creativity and engagement in teaching and learning endeavors. Research conducted at SMK Swasta Pelita Bulu Cina focuses on harnessing consumables to enhance student creativity and serve as educational aids, thereby promoting eco-friendly learning mediums. The research methodology incorporates training, practical application, and socialization efforts. Findings indicate that integrating consumables into learning activities enlivens classroom dynamics, capturing students' interest and attention, particularly when they actively participate in crafting their educational materials. This approach empowers teachers to innovate within the classroom, fostering a more dynamic learning environment and mitigating student disengagement. Consequently, consumables offer a viable strategy for enhancing student involvement and preventing monotony in the learning process.